Evaluasi Pengendalian Waktu dengan Metode Time Cost Trade Off pada Proyek Fiberline Building And Relocation New Area Woodyard - Handayani, Elvira; Immanuddin, M. (Universitas Batanghari, 2023)
Projects generally have a deadline, meaning that the project must be completed before or on time. In connection with this project problem, the success of a project can be measured from three things, namely, cost, quality and timeliness of completion. Many efforts must be made in order to achieve what has been planned, including calculating the correct strength of the structure, calculating cost estimates that are effective and economical. In implementing the construction of the Fiberline 3 Building (FL3B) & Relocation New Area Woodyard PT project. Riau Andalan Pulp And Paper indicated that there was a delay in the Excavation, Bacfilling & Cutting/Breaking Top Of Pile work, therefore the researchers accelerated it by rescheduling. This is intended so that this project can be completed according to the planned target. The method that will be used to speed up the duration of the project in this research is the Time Cost Trade Off method or also called the cost versus time exchange method. Based on the results of the Time Cost Trade Off Analysis on the Fiberline 3 Building project (FL3B) & Relocation New Area Woodyard PT. Riau Andalan Pulp And And Paper, it can be concluded as follows: Acceleration of project duration for the alternative of increasing overtime working hours by 4 (four) hours is obtained:The optimum time to accelerate the project duration is 142 calendar days with an increase in direct costs from Rp. 3,145,559,610.00 to Rp. 3,346,947,482.50. The total optimum project cost due to accelerated project duration increased from Rp. 3,806,175,528.10 to Rp. 4,007,523,400.60. Acceleration of project duration for the alternative of increasing the number of workers was obtained. The optimum time for accelerating the project duration was 142 calendar days with an increase in direct costs from Rp. 3,145,559,610.00 to Rp. 3,220,683,352.66 Total optimum project costs due to accelerated project duration increased from Rp. 3,806,175,528.10 to Rp. 3,881,259,270.76.